2018
DOI: 10.1111/1752-1688.12615
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability, Sensitivity, and Uncertainty Analyses of the BANCS Model Developed to Predict Annual Streambank Erosion Rates

Abstract: Accelerated streambank erosion caused by channel instability can be the leading cause of sediment impairment of streams. Obtaining accurate streambank erosion rates for sediment budgeting and prioritizing mitigation efforts can be difficult and costly. One approach to quantifying streambank erosion rates is through the development and implementation of an empirically derived “Bank Assessment for Non‐point Source Consequences of Sediment” (BANCS) model. This study aims to improve the BANCS model application by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…We also agree that the BANCS field methods are sensitive to observer variation, but we consider that to be a limitation of the BANCS model itself, as shown by the study cited by the discussants (Bigham et al. ), and not specifically of our study in which observations were always made by more than one person.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…We also agree that the BANCS field methods are sensitive to observer variation, but we consider that to be a limitation of the BANCS model itself, as shown by the study cited by the discussants (Bigham et al. ), and not specifically of our study in which observations were always made by more than one person.…”
supporting
confidence: 80%
“…A recent publication by Bigham et al. () also recognized this lack of detailed procedures for BANCS. Hopefully that shortcoming will soon be remedied so that the BANCS model can be uncontroversially evaluated.…”
mentioning
confidence: 99%
“…In studies, where there was a weak relationship reported (Ghosh et al, 2016;Harmel et al, 1999;Kwan and Swanson, 2014), the authors used only visual assessments for bank parameters, whereas we used the sieve and densimetric tests to determine the bank material, and a laser clinometer to determine the bank angle. As Bigham et al (2018) state, inaccurate determination of these parameters (especially study bank height, root depth, bank angle, and bank material) affects the estimation of the erodibility potential, thus affecting the relationship between the potential and the real erosion.…”
Section: Resultsmentioning
confidence: 99%
“…() were looking at observer variation in stream classification, observer variation and its impact on BEHI and NBS determinations were examined by Bigham et al. (). Here, study bank height was determined to be the most sensitive BEHI parameter in observer variation.…”
Section: Introductionmentioning
confidence: 99%
“…Bigham et al. () also found “The uncertainty of the bank material adjustment was determined to contribute the most to the uncertainty of the overall BEHI rating results” (p. 436). McMillan et al.…”
Section: Introductionmentioning
confidence: 99%